Continuous Militarization as a Mode of Governance of Indigenous People in the Russian Arctic - Vladimirova, Vladislava (Politics and Governance, 2024)
This article analyzes ethnographic data that shows long-term militarization forms a significant part of state governance of the population and environment in the Arctic. Kola Peninsula, the study region, is a borderland with the West and has since the 1950s been a heavily militarized area. Applying insights from research on militarization, subjectivities, materiality, borders, and regionalism in autocratic regimes, I show how militarization shapes the environment and the lives of Indigenous reindeer herders. Despite discourses of demilitarization in the 1990s, Kola Peninsula did not move away from militarization as part of governance. The article explores what I call continuous militarization by engaging with two phenomena: (a) fencing off territories for military use and infrastructure, and (b) nuclear pollution. It discusses the interrelations of materiality and knowledge in maintaining Indigenous subjectivities and culture in line with the objectives of militarization, and shows how Russia uses participation in the Barents Euro-Arctic Region to support the objectives of militarization and justify them to the local population. The article finds that militarization is employed by the authorities to solidify the current autocratic regime among residents in the Arctic.